Regulatory culture and architectural project - Losasso, Mario (TECHNE - Journal of Technology for Architecture and Environment, 2024)
In architecture, the dialectics between regulation and design belong to a very broad field of objects, tools, characteristics, performance, relations and behaviours. It is necessary to refer to these aspects in defining prefigurative, design or management actions in interventions on the built environment. In general, regulations establish a system of values to which they can be compared, starting from a theoretical and methodological field, and then moving on to areas ranging from knowledge to the effects on the territories. Unlike the rule, which provides its meaning in the act of observing it, the regulation has a dual aspect. The first concerns an imperative and precept formulation, the second the reference to custom or practice. Hence, it oscillates between binding prescription and non-binding information levels or recommendations. Through the regulatory action, architecture has constantly strived to remove itself from arbitrary conditions. Normative frameworks define principles and rules, including both unplanned ones, as well as decision support tools like manuals and technical information, specifications and regulations. These standards manage various aspects of control and management of the multiple qualities of architecture. Within the building process, the standard finally expresses the collective needs to define a regulatory mechanism capable of avoiding conflicts between various subjects, needs and instances. The evolution of normative culture has shifted from a system of objective regulations, aimed at defining characteristics and functions of specific building objects to rationalise what exists, to more flexible regulations that are predominantly suggestions for performance. These performance standards focus on meeting specific spatial, technical and environmental requirements an ‘object’ must provide at the moment of its use. They are attentive to a quality that does not depend on construction solutions or on techno-typological, morphological or physical-chemical characteristics, but which is linked to a system of needs to be satisfied, the outcome of the interaction between construction and cultural, socio-economic and environmental context. Today’s regulatory landscape has expanded, increasing sensitivities to environmental challenges, health and the qualities of living space. There has been a shift from regulation through standards and deterministic technical-constructive prescriptions to performance standards and a regulatory space, which is more open today, and which interacts with emerging issues. In our country, university research on regulatory culture has long featured the technological culture of design, production and building processes, with the contribution of numerous theoretical and applicative studies. In the most recent concepts, approaches based on sets of measurable indicators and application criteria are being successfully explored through the verification of compliance with reference values, predetermined requirements and objectives to be achieved. This allows a greater interest on process results and spin-offs, and not only on the qualities of the output produced. Today, the implementation of sustainability issues has widened the scope to directives, laws, standards and certifications. The relationship between design and regulations is developed with a broad reference to the multiple levels of standardisation according to mechanisms such as those expressed by the operational sequence of European directives for member states to which national laws must conform, progressively assuming levels of cogency. In recent years, the framework of legislative devices has been given considerable impetus by the advancement of issues on the quality of design and construction, as well as on the protection of the environment and people’s health. Finally, the regulation of the management of urban and housing complexity has opened up the field to both general and detailed standardisation processes. Additionally, in recent years, the energy, climate and geopolitical emergencies have generated a highly articulated chain of regulations, both guideline and mandatory. The important ministerial action of reorganising regulatory devices was also implemented by bringing specific specialised regulations within general frameworks (such as the Consolidated Text on Construction, the legislative device on urban regeneration or land consumption). On a national level, plans and programmes, which can potentially be identified as guidelines for executive planning, have become increasingly important. An example is provided by what will be the transition from the recently adopted – on 22.12.2023 – PNACC – Piano Nazionale di Adattamento ai Cambiamenti Climatici (National Climate Change Adaptation Plan) to the implementation of climate adaptation strategies and actions to be developed at regional and local scales. Another level of standardisation concerns addresses, guidelines and performance standards defined within ministerial calls for tenders. Innovation concerning such calls is also emphasised in the effects on territories. In this case, the regulatory scenario gives value to the process, rather than to the product-project alone. The PINQuA – Programma Innovativo Nazionale per la Qualità dell’Abitare (National Innovative Programme for the Quality of Living) provides a significant example of this aspect. In fact, the innovative elements in this programme include the introduction of a rewarding approach based on results and performance measured through criteria that, going beyond the conventional evaluation referring only to the project output, focus on the effects and fallouts of complex integrated actions. The theme of guidelines and checklists for public bodies is a type of standardisation to support decision-making through various stages such as control, verification, validation, feasibility and congruence. The emphasis on qualifying the products of activities related to the new scenarios introduced by the PNRR, the National Recovery and Resilience Plan, deserves attention for several aspects. One notable aspect is the adoption of the regulating principle of ‘do no significant harm’ (DNHS), along with the choice to link together the numerous intervention proposals aimed at implementing structural and lasting changes in the built environment, both in terms of implementation and methodology. Cognitive, simulative or prefigurative activities are oriented in their feasibility and compliance with preliminary requirements and measurable effects, framed in a circular vision with feedback processes. Currently, there is a great push towards environmental standards, extended in a multi-scalar approach that includes multiple aspects ranging from urban regeneration to certification and CAM – Minimum Environmental Criteria. Finally, a specific discourse should be made on the European directives that play a relevant role in defining ‘frameworks’, as in the case of the directives “Case green”, “Fit for 55” or even “REPowerEU”, within which the implementing regulatory frameworks must be defined. The above reveals a more integrated relationship between numerous systems and levels of standardisation, characterised by varying scalar approaches and different procedural components and sequences. Hence, the theme “Project and Standard” brings the focus of the TECHNE journal back to the aspect of the project. In its component of architectural culture, technical thinking, procedure and process-related implementation, with regard to the standard, the project must be included in a circular process with numerous moments of interaction and validation, which pose important issues that can be framed in the relationship between regulatory updates and levels of controlled simplification by introducing guiding strategies and greater flexibility.